The Impact Of Outsourcing on Hotel Efficiency and Performance - Wangsa, Vanessa; Erwen, Ivana Valencia; Natasha, Sharren; Shielline, Patricia; Poluan, Regina Calista; Wulandari, Nuraeni; Kalfin, Kalfin (International Journal of Humanities, Law, and Politics, 2024)
Outsourcing has become a commonly used strategy in the hotel industry to improve operational efficiency and hotel performance. Hotel performance is very important in maintaining the quality of service provided to consumers. Therefore, this research aims to find out the impact of the use of outsourcing on the efficiency and performance of hotels in the Gading Serpong area. In this research, the data used is hotel data in Gading Serpong. The method used in the research is a qualitative method. Based on the research results, it was found that outsourcing has a big influence on hotel efficiency and performance. The number of hotels in the Gading Serpong area is 8 hotels with a classification of 1 to 5 stars. Every hotel in the Gading Serpong area uses outsourcing as a resource to help meet customer satisfaction by increasing hotel efficiency and performance. These findings provide valuable insights for hotel managers in designing strategies to improve their efficiency and performance. As a result, it is hoped that this research can become an important reference for the hotel industry, especially for hotel managers in the Gading Serpong area, in optimizing the use of outsourcing to improve customer experience and strengthen their market position.